The New Human Agenda: An Empowering Approach to Poverty Alleviation - Raphaely, Talia; Marinova, Dora (Murdoch University, 2006)
The ways of the West are not necessarily the best for releasing human potential and capacity for poverty alleviation. This paper puts forward the New Human Agenda, built around the concepts of increased humanness, partnerships and bioregionalism, as an alternative approach to traditional interventions. Using the example of The Hunger Project, it argues that the applied process and strategies (which are locally conceived, dynamically transformative, flexible, connected, iterative, engaging, participatory and empowering) have the potential to deliver sustainable and long term opportunities for poverty alleviation.